Influence of the mineral content of the seston on tropical cladocerans of a marginal lake. - Fileto, Claudia; Henry, Raoul; Arcifa, Marlene Sofia; Ferreira, Rosa Antonia Romero (My University, 2010)
Bioassays were carried out seasonally to evaluate individual growth and reproduction of cladocerans, from a marginal lake, with the addition of nitrogen (N), phosphorus (P), and both N and P to natural seston; Methods: Cohorts originated from cultivated females were submitted to the following treatments: 1) lake seston, 2) lake seston + P, 3) lake seston + N, and 4) lake seston + NP; Results: The sestonic C:P and C:N molar ratios were always high and limiting, according to threshold ratios estimated for temperate lakes. P addition to seston enhanced the growth rates of one species, D. birgei. A significant higher growth rate of B. longirostris was found in the seston enriched with N compared to natural seston, as well as a higher fecundity of M. minuta. The fecundity of D. birgei was significantly higher in the seston enriched with both N and P. C, N, and P body content of cladocerans was similar to that of temperate counterparts; Conclusion: Energy limitation related to carbon content or food quality seems to be most important in controlling cladocerans' populations in the lake than food mineral content.

Objetivo: Foram realizados experimentos para avaliar o crescimento individual e a reprodução de cladóceros de uma lagoa marginal com a adição de nitrogênio (N), fósforo (P) e fósforo e nitrogênio juntos ao séston natural; Métodos: Os experimentos foram realizados sazonalmente. Coortes originadas de fêmeas cultivadas foram submetidas aos seguintes tratamentos: 1) séston do lago, 2) séston do lago + P, 3) séston do lago + N e 4) séston do lago + NP; Resultados: As razões molares C:P e C:N do séston estavam sempre altas, de acordo com razões estimadas para lagos temperados. A adição de P ao séston aumentou somente o crescimento de D. birgei. No entanto, a fecundidade de B. longirostris foi significativamente maior no tratamento do séston enriquecido com N comparado ao séston sem adições, assim como a fecundidade de M. minuta. A fecundidade de D. birgei foi significantemente maior no séston enriquecido com N e P. O conteúdo corporal de C, N e P dos cladóceros foi similar ao encontrado para cladóceros de região temperada; Conclusão: A limitação por energia relacionada ao conteúdo de carbono ou à qualidade do alimento parece ser mais importante no controle das populações de cladóceros no lago comparado ao conteúdo mineral do alimento.
Influência do contéudo mineral do seston em cladóceros tropicais de uma lagoa marginal